(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The article discusses the features of the development of leasing, taking into account international experience. Based on the experience of the American and Western European leasing market, analysis of the operating activities of foreign leasing companies, the theoretical foundations of investment financing from external financial sources using the international leasing mechanism are presented. The article reveals the features of the investment financing mechanism based on the international leasing scheme, taking into account the acceptability of financing conditions, both for the enterprise-lessee and for the company-lessor. Attention is drawn to the possibility of external financing of such a leasing transaction with the involvement of investors and the issue of bonds on the open securities market. Leasing will allow not only to update the fixed assets of a number of leading industries, but also to solve the problem of financing this process at the same time. International experience of leasing application plays an important role in this. Without requiring large one-time expenses of their own funds from enterprises, leasing at the same time guarantees the purposeful development of financial resources, which ultimately will allow attracting into the industry the opportunities of the Russian capital market that have not been fully utilized so far, as well as funds from foreign investors.